Évaluation de la prolifération de la Jacinthe d’eau du lac Ravelobe Ankarafantsika et plan de restauration - Ranarijaona Hery Lisy Tiana; Zainabo Félicie; Andriamanantena Ainazo Herilala; Andrianasetra Georges Simon (VertigO)
The floating water hyacinth or Eichhornia crassipes invades Madagascar waters lotics and lentics. It’s the case of the lake Ravelobe, inside the national park of Ankarafantsika Mahajanga Madagascar, which, besides crocodiles, is very renowned by its wealth endemic in fishes, amphibians, aquatic turtle, and birds. In spite of the measures taken by the persons in charge of the park in 2007, by manual eradicated of the hyacinth by the villagers, the hyacinth proliferates in important scale. Regulation’s methods of the invasive species, besides quadrat and transects are applied to the plant, with the aim of estimating their ecology and the proliferation. Stable, the hyacinth invades almost half of the lake in wet season : it’s monospecific in many aquatics zones, or retained by the stalks of helophytes ; forms a nursery in the river which feds the lake. Entailed by the wind, it invades in a scattered way the entire free surface’s water. Ten plant groups were listed, all associated with Eichhornia crassipes. Three ecological factors are responsible in their distribution. Both maps of vegetations in wet and dry season represent the distribution of hyacinth with their species associate. The biomass as well as the density of hyacinth are important. The lake is filled because of the degraded basin hillsides’s erosion. The lake takes a convex aspect. The river which feds the lake searches an outcome deviant to feed the lake. The fragmentation of the ecosystem Ravelobe is felt. Human and birds have difficulties to fish within the water hyacinth proliferated. Recommendations are advanced to regulate water hyacinth and maintain the biodiversity.